2020
DOI: 10.1097/sga.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening Practices Among Texas Nurse Practitioners and Physician Assistants

Abstract: The purpose of this study was two-fold: (1) To describe and compare Texas Nurse Practitioners' and Physician Assistants' knowledge and use of current screening guidelines for individuals at varying risk for colorectal cancer and (2) to compare their recommendations for referral for genetic counseling for persons at increased risk for colorectal or endometrial cancer. The study used a descriptive correlational comparative design. A self-administered web-based survey was sent to the members of the Texas Nurse Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Kurtzman et al, 2017 [ 26 ] Compare the quality of care and practice patterns of NPs, PAs, and primary care physicians in health centres USA National Primary care 104 Longitudinal (repeated cross- sectional surveys) Referrals to other physicians Physical examination Reconsultation Low 11. Laird et al, 2020 [ 27 ] 1) describe and compare Texas NP & PA knowledge and use of screening guidelines for colorectal cancer 2) compare recommendations for referral for genetic counselling for colorectal or endometrial cancer USA Texas Primary care n/a Cross-sectional (survey) Screening High 12. Liu et al 2017 [ 28 ] What impact NPs and PAs have on utilization in a setting where physician-supervised NPs and PAs provide face-to-face primary care USA Georgia Primary care 10 Quasi-experimental (medical records) Diagnostic tests ordered Referrals to other physicians ED visits Medium 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurtzman et al, 2017 [ 26 ] Compare the quality of care and practice patterns of NPs, PAs, and primary care physicians in health centres USA National Primary care 104 Longitudinal (repeated cross- sectional surveys) Referrals to other physicians Physical examination Reconsultation Low 11. Laird et al, 2020 [ 27 ] 1) describe and compare Texas NP & PA knowledge and use of screening guidelines for colorectal cancer 2) compare recommendations for referral for genetic counselling for colorectal or endometrial cancer USA Texas Primary care n/a Cross-sectional (survey) Screening High 12. Liu et al 2017 [ 28 ] What impact NPs and PAs have on utilization in a setting where physician-supervised NPs and PAs provide face-to-face primary care USA Georgia Primary care 10 Quasi-experimental (medical records) Diagnostic tests ordered Referrals to other physicians ED visits Medium 13.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies explicitly linked care delivery with quality, by examining ordering of guideline-discordant tests or unnecessary referrals [ 24 ] or by scoring performance on clinical vignettes [ 25 ]. Seven studies reported on tasks related to cancer screening, specifically breast, ( n = 3) [ 25 , 25 , 26 ], colorectal ( n = 3) [ 26 , 27 , 27 ]) cervical ( n = 2) [ 28 , 29 ], prostate ( n = 1) [ 29 ], and endometrial cancer ( n = 1) [ 30 ]. (Table 2 ) PA competence and skills …”
Section: Resultsmentioning
confidence: 99%
“…Kapsamlı bakım sağlamak için risk altındaki bireylerin tarama ve eğitimlerine önem verilir. Birinci derece hasta yakınlarına düzenli aralıklarla kolon kanseri taraması yaptırmanın önemi açıklanır (Akyolcu ve ark., 2020;Gustafsson et al, 2019;Karadağ & Bulut, 2019;Laird & Raudonis, 2020;Moe, 2020;Thanikachalam & Khan, 2019). Ayrıca hastalara verilecek psikolojik destek, hastalık ve ilgili eğitimlerin, kansere bağlı stres ve endişeleri azalttığı, gevşeme becerilerini geliştir-diği ve hastalığın tekrarlama riskini azalttığı, uygun izleme ve tarama davranışları geliştirmede fayda sağlayabildiği belirtilmektedir (Zhang et al, 2020).…”
Section: Kolorektal Cerrahi Süreç Sonrası Taburculuk Eğitimi Kapsamıunclassified
“…19 Seven studies reported on tasks related to cancer screening, speci cally breast, (n = 3) 18 20 27 , colorectal (n = 3) 29 , 26 18 ) cervical (n = 2) 30 18 , prostate (n = 1), 21 and endometrial cancer (n = 1). 29 (Table 2)…”
Section: Findings 1 Pa Deployment On Tasks To Support Cancer Diagnosismentioning
confidence: 99%